Jews in Poland-Lithuania in the Eighteenth Century. - Hundert, Gershon David (University of California Press, 2004)
Missing from most accounts of the modern history of Jews in Europe is the experience of what was once the largest Jewish community in the world--an oversight that Gershon David Hundert corrects in this history of Eastern European Jews in the eighteenth century.